2019
DOI: 10.12659/msm.916939
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181c Suppresses the Biological Progression of Osteosarcoma via Targeting SMAD7 and Regulating Transforming Growth Factor-β (TGF-β) Signaling Pathway

Abstract: Background Osteosarcoma is a primary bone aggressive cancer, affecting adolescents worldwide. Increasing evidence suggests that dysfunction of microRNAs (miRNAs) plays a pivotal role in malignancies. The aim of this study was to evaluate the potential functions of miR-181c and verifying its regulatory effects on SMAD7 in osteosarcoma. Material/Methods The expressions of miR-181c and SMAD7 in osteosarcoma were detected by quantitative real-time polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…SMAD7, a member of SMAD family, is reported to be associated with the development of a variety of cancers. Recent studies have shown that SMAD7 is present in common malignancies and acts as a tumor suppressor, including lung cancer, liver cancer, gastric cancer, bladder cancer, triple negative breast cancer, and osteosarcoma [11,[23][24][25][26][27][28]. In CRC, reduced level of SMAD7 is found to be involved in the process of cancer growth as well as the process of EMT and invasion [29].…”
Section: Discussionmentioning
confidence: 99%
“…SMAD7, a member of SMAD family, is reported to be associated with the development of a variety of cancers. Recent studies have shown that SMAD7 is present in common malignancies and acts as a tumor suppressor, including lung cancer, liver cancer, gastric cancer, bladder cancer, triple negative breast cancer, and osteosarcoma [11,[23][24][25][26][27][28]. In CRC, reduced level of SMAD7 is found to be involved in the process of cancer growth as well as the process of EMT and invasion [29].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of osteosarcoma, it was found that a decrease in miR-181c expression level was associated with a poor prognosis and malignant clinical and pathological features. As a result of functional studies, it was shown that activation of miR-181c dramatically inhibited the proliferation, invasion and migration of osteosarcoma cells [77]. It was also revealed that the SMAD7 gene was a direct functional target for miR-181c in osteosarcoma cells and that overexpression of miR-181c suppresses the signaling pathway of EMT and TGF-β in osteosarcoma cells through regulation of SMAD7 [77].…”
Section: Downregulated Micrornas Associated With Lymphatic Disseminatmentioning
confidence: 99%
“…As a result of functional studies, it was shown that activation of miR-181c dramatically inhibited the proliferation, invasion and migration of osteosarcoma cells [77]. It was also revealed that the SMAD7 gene was a direct functional target for miR-181c in osteosarcoma cells and that overexpression of miR-181c suppresses the signaling pathway of EMT and TGF-β in osteosarcoma cells through regulation of SMAD7 [77]. Significant downregulation of miR-181c was also detected in the case of hepatocellular carcinoma when compared with normal tissues.…”
Section: Downregulated Micrornas Associated With Lymphatic Disseminatmentioning
confidence: 99%
“…Interestingly, distinct miRNA variants derived from the same precursor can affect SMAD7 gene expression in different cell types. For example, from the miR-181 precursor four mature miRNAs can be produced: miR-181a, miR-181b, miR-181c or miR-181d, of which MiR-181a was found to induce repression of its functional target SMAD7 in ovarian cancer cells to promote TGFb-mediated epithelial-to-mesenchymal transition (EMT) (Parikh et al 2014), whereas MiR-181c downregulated SMAD7 expression in neuroblastoma and osteosarcoma (Li et al 2014;Fu et al 2019). Additionally, miR-181 variants have been shown to regulate T cell phenotype in autoimmune neuroinflammation by directly targeting SMAD7 mRNA (Ghorbani et al 2017;.…”
Section: Smad7 Regulation By Diverse Mirnasmentioning
confidence: 99%
“…MiRNAs regulating SMAD7 expression in the context of disease a . ,miR-15a, miR-18a, miR-20a, miR-21, miR-25, miR-32, miR-92a/b, miR-93, miR-106a, miR-106b $25, miR-130b, miR-132, miR-181, miR-182, miR-185, miR-195, miR-216a, miR- 324, miR-367, miR-424, miR-452, miR-497, miR-503, MiR-519d, miR-520g/h, miR-543, miR-663b, miR-1269, miR-2909, miR-4775 (Smith et al 2012Chen et al 2013;Li et al 2013;Xia et al 2013;Chang et al 2013;Li et al 2014;Parikh et al 2014;Yu et al 2014;Kan et al 2015;Liu et al 2015;Tang et al 2015;Bu et al 2015;Wang et al 2015;Xu et al 2015;Hu et al 2016;Zhuang et al 2016;Liu et al 2016;Duan and Chen 2016;Dai et al 2016;Yu et al 2016;Ratz et al 2017;Tong et al 2017;Zhao et al 2017;Wang et al 2017;Wang 2017;Ayub and Kaul 2017;Hujie et al 2018;Chen et al 2018;Zhai et al 2018;Fu et al 2019;Huang et al 2019;Shen et al 2019; This table includes SMAD7-regulating miRNAs from homo sapiens, mus musculus and rattus norvegicus.…”
mentioning
confidence: 99%